Ultrasonic full-matrix imaging of curved-surface components. (1st December 2022) - Ji, Kaipeng; Zhao, Peng; Zhuo, Chaojie; Chen, Jian; Wang, Xianghong; Gao, Shiquan; Fu, Jianzhong
Highlights: An ultrasonic method is developed to image defects in components with curve surfaces. The frequency-domain reverse time migration is unrestricted to the surface shape. Numerical and laboratory experiments are conducted for the method validation. The method overperforms than the existing methods in the imaging quality. The method to remove direct wave and the imaging conditions are fully investigated. Abstract: Curved-surface components (CSC) are ubiquitous in engineering practice such as automobiles, aerospace and pipelines. However, they are prone to void and crack defects which greatly degenerate mechanical properties and are badly in need of effective detection. Ultrasonic full-matrix imaging is a conspicuous method in nondestructive testing. However, the research on high-quality imaging of CSC is still limited. In this paper, an ultrasonic imaging method based on frequency-domain reverse-time migration (FD-RTM) is developed for CSC at the first attempt, unrestricted to the surface shape of components. Through discretization of the acoustic wave equation in the frequency domain, the wavefields of all excitations are extrapolated together to obtain the source and received wavefields at each frequency. After implementation of the imaging conditions, the high-quality image of the defects is obtained. The efficaciousness of the method was examined with the numerical simulation and laboratory experiment, in both of which the void and V-shaped crack defects in copper and aluminum CSCs were imaged in high quality. Results have proven that FD-RTM has obvious advantages over the existing imaging methods for CSC. Therefore, the proposed method shows great potential in defect detection for CSC in various fields.